COPD associated pulmonary hypertension: A post hoc analysis of the PERFECT study - Steven D. Nathan; Victoria Lacasse; Heidi Bell; Prakash Sista; Michael Di Marino; Todd Bull; Victor Tapson; Aaron Waxman (Pulmonary Circulation)
Abstract The PERFECT study, a randomized, controlled, double‐blind study of inhaled treprostinil in patients with COPD and associated pulmonary hypertension (PH‐COPD) was a negative trial that was terminated early. The reason(s) for the negative outcome remains uncertain. A post hoc analysis of data from the PERFECT study was undertaken to identify adverse responders and possibly potential responders. The goal was also to provide insight into phenotypes for possible inclusion and exclusion in future PH‐COPD clinical trials. An adverse response on active treatment was seen in 36.4% (24/66) of the subjects compared to 27.6% (16/58) on placebo. There was no evidence to suggest that hyperinflation, bronchospasm, or occult heart failure played any role in the untoward outcomes of the study. The patients who died during the study all had baseline diffusing capacity for carbon monoxide ≤25% of predicted. Evidence of a potential response was seen in 10.6% (7/66) of the patients who received inhaled treprostinil. Patients who had evidence of a treatment response had a baseline mean pulmonary artery pressure of ≥40 mmHg and a forced expiratory volume in the first second of ≥40%. Change in N‐terminal prohormone of brain natriuretic peptide did not predict clinical response. This post hoc analysis provides information that may potentially enable improved selection of patients for future therapeutic trials in PH‐COPD. These analyses are post hoc, observational, and exploratory. The thresholds defining the spectrum of responders are preliminary and may require further refinement and validation in future studies.